Merging English into Sport in Aerobic Exercise Based on Content-Based Instruction - Suraya, Fatona; Ali, Mohammad Arif; Anggita, Gustiana Mega; Kalisa, Pasca (Universitas Negeri Semarang, 2018)
A research on merging English into Sport in Aerobic Exercise based on Content-Based Instruction (CBI) was conducted related to the need of the aerobics instructor who can lead the class in English especially with the present of Asean Economic Market in the end of 2015. The problem being evaluated in this paper was ―is there any difference influence between CBI learning model and conventional learning model to the aerobics instructor performance in English? The aim of this research is to evaluate the different influence between CBI learning model and conventional learning model to the aerobics instructor performance in English. 20 students of Semarang State University and Wahid Hasyim University were grouped into 2 groups. One is CBI group and the other ones is conventional group. The treatment was conducted for 6 weeks, 12 meetings. The result showed that the significant score for CBI group is 0,005<0, 05, meaning H1 is accepted. Therefore there is a significant difference between those who have been taught using CBI to those who have been taught using conventional learning for the aerobics instructor performance in English.